Normal Values of Thyroid Uptake of 99mTechnetium Pertechnetate SPECT in Mice with Respect to Age, Sex, and Circadian Rhythm - Beindorff, Nicola; Bartelheimer, Annika; Huang, Kai; Lukas, Mathias; Lange, Catharina; Huang, Eleonore L.; Aschenbach, Jörg R.; Eary, Janet F.; Steffen, Ingo G.; Brenner, Winfried (Nuklearmedizin - NuclearMedicine, 2018)
Aim: The aim of this study was to establish normal values for thyroid uptake of 99mtechnetium pertechnetate (99mTcO4) as a function of age, sex and circadian rhythm in mice.Methods: In 12 female (F) and 12 male (M) C57BL/6N mice, nine consecutive SPECT images of 10 min duration each were acquired as dynamic acquisitions beginning 5 min after intravenous injection of 80 MBq 99mTcO4. Each mouse was imaged in follow-up studies up to 24 months (A: 1 month; B: 3 months; C: 6 months; D: 12 months; E: 24 months). In order to assess for physiologic changes related to circadian rhythm, animals were imaged during light (sleeping phase, SP) as well as during night conditions (awake phase, AP). The percentage tracer uptake of the injected activity is expressed as median %ID.Results: Female mice showed significantly higher uptake than males (F 1.6, M 1.1; p < 0.001). This effect was observed up to the age of 12 months: A (F 1.6, M 1.1; p < 0.001), B (F 1.7, M 1.1; p < 0.001), C (F 1.8, M 1.2; p < 0.001), D (F 1.6, M 1.2; p < 0.001), E (F 1.1, M 1.1; p = 0.79). Impact of age on uptake could be observed in females (p = 0.056) and was not present in males (p = 0.27). A significant effect of circadian rhythm could not be observed in females (SP 1.6, AP 1.7; p = 0.65) but in males (SP 1.2, AP 1.1; p = 0.02).Conclusion: This study showed a significant influence of sex on thyroid 99mTcO4 uptake in mice. Sex was also a significant factor affecting age-related changes in uptake in female mice but not in males. In contrast, circadian rhythm had no relevant impact on 99mTcO4 uptake. Therefore, design of thyroid uptake studies in mice using 99mTcO4 should consider animal sex, and in females, age as significant factors affecting uptake.Ziel: Ziel dieser Studie war die Erhebung von Normwerten für den Schilddrüsen Uptake von 99mTechnetium-Pertechnetat (99mTcO4) in Abhängigkeit von Alter, Geschlecht und circadianem Rhythmus bei Mäusen.Methoden: Bei 12 weiblichen (F) und 12 männlichen (M) C57BL/6N Mäusen wurden neun konsekutive SPECT Akquisitionen von jeweils 10 min Dauer 5 min nach intravenöser Injektion von 80 MBq 99mTcO4 durchgeführt. Jede Maus wurde mehrmals bis zu 24 Monaten untersucht (A: 1 Mo; B: 3 Mo; C: 6 Mo; D: 12 Mo; E: 24 Mo). Um Veränderungen auf Grund des circadianen Rhythmus zu erfassen wurden die Tiere während der Hellphase (Schlafphase, SP) sowie während der Dunkelphase (Wachphase, AP) untersucht. Der prozentuale Tracer Uptake ist als Median %ID der injizierten Aktivität aufgeführt.Ergebnisse: Weibchen zeigten einen signifikant höheren Uptake als Männchen (F 1,6, M 1,1; p < 0,001). Dieser Effekt wurde bis zu einem Alter von 12 Mo beobachtet: A (F 1,16, M 1,1; p < 0,001), B (F 1,7, M 1,1; p < 0,001), C (F 1,8, M 1,2; p < 0,001), D (F 1,6, M 1,2; p < 0,001), E (F 1,1, M 1,1; p = 0,79). Ein altersabhängiger Einfluss zeigte sich bei Weibchen (p = 0,056), jedoch nicht bei Männchen (p = 0,27). Ein signifikanter Effekt des circadianen Rhythmus konnte bei Männchen (SP 1,2, AP 1,1; p = 0,02) nicht aber bei Weibchen (SP 1,6, AP 1,7; p = 0,65) beobachtet werden.Schlussfolgerung: Diese Studie zeigt einen signifikant geschlechtsabhängigen Einfluss auf den Schilddrüsen Uptake von 99mTcO4 bei Mäusen. Im Gegensatz zu Männchen treten bei Weibchen altersabhängige Veränderungen im Uptake auf. Dagegen hat der circadiane Rhythmus keinen relevanten Einfluss. Folglich sollte bei dem Design von Schilddrüsenuntersuchungen mit 99mTcO4 bei der Maus Geschlecht und bei weiblichen Tieren auch Alter als signifikante Faktoren berücksichtigt werden.
Keywords: Age; sex; circadian rhythm; SPECT; technetium uptake; thyroid; estrous cycle